LIS and Other Knowledge Domains: Interdisciplinary of LIS Scholars’ Publications - Pluzhenskaya, Marina (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This pilot study focuses on a balance between importing and exporting qualities of LIS. The collected data leads to the conclusion that importing qualities of LIS are still prevailing though rapid change in information technologies attracted attention of scholars and practitioners from many disciplines to LIS. The fact that almost… Ce projet pilote porte sur l’équilibre entre l’importation et l’exportation de citations liées à la BSI. Les données recueillies mènent à la conclusion que l’importation de citations de la BSI prévaut toujours, même si des changements rapides dans les technologies de l’information ont attiré l’attention des chercheurs et des praticiens de plusieurs disciplines sur la BSI. Puisque que…